T5 Pregnancy zone protein is released into neutrophil extracellular traps in severe bronchiectasis. (12th November 2019) - Finch, S; Shoemark, A; Dicker, AJ; Keir, HR; Smith, A; Fardon, TC; Cassidy, D; Huang, JTJ; Chalmers, JD
Abstract : Introduction: Pregnancy zone protein (PZP) is a broad spectrum immunosuppressive protein originally discovered in the serum during pregnancy and believed to prevent foetal rejection. We unexpectedly identified PZP as highly expressed in sputum from patients with bronchiectasis and chronic Pseudomonas aeruginosa infection. In this study we aimed to characterise PZP in the bronchiectasis airway including its relationship with disease severity. Methods: Patients were recruited from a specialist bronchiectasis clinic. PZP was measured in sputum and serum using ELISA. The sputum microbiome was characterised using 16s rRNA sequencing. A combination of Immunofluorescence, ELISA, electron microscopy and an in-vivo Staphylococcus aureus infection model were used to study dynamics of PZP release in the lung. Results: Liquid chromatography/mass spectrometry in 20 patients identified 80 proteins that were differentially expressed between P.aeruginosa infected vs uninfected individuals, including PZP which was higher in P. aeruginosa infected patients. Results were validated in a cohort of 124 bronchiectasis patients where PZP was associated with severity of disease using the bronchiectasis severity index – median sputum PZP 163 µg/ml (IQR 64.61-854.1) compared to mild (58.58µg/ml (IQR 25.29-163.8), or moderate disease (52.64 (IQR 24.09-97.34), (p<0.001). Sputum PZP was higher in patients who were culture positive for P. aeruginosa and was correlated to Pseudomonas operational taxonomic units in the microbiome. PZP was related to bacterial load and could be reduced with antibiotic therapy in a substudy of 20 patients during acute exacerbation. PZP was released from peripheral blood neutrophils stimulated with PMA, fMLP and bacteria in a dose dependent manner and was released into BAL during acute neutrophilic inflammation using a murine S. aureus infection model. Electron Microscopy imaging of neutrophils demonstrated that PZP is present in the cytoplasm and nuclei of neutrophils and fluorescence microscopy also demonstrated PZP associated with neutrophil extracellular traps (NETs) in-vitro, and PZP correlated with neutrophil extracellular traps in-vivo. Conclusion: PZP is a novel neutrophil protein released during neutrophil extracellular trap formation and is a biomarker of bronchiectasis severity.